Defining Engaged Buddhism: Traditionists, Modernists, and Scholastic Power - Temprano, Victor Gerard (Buddhist Studies Review, 2014)
Thomas F. Yarnall’s 2003 categories of ‘modernist’ and ‘traditionist’, used to classify accounts of the origins of engaged Buddhism, have proven useful as methodological tools but today need considerable reevaluation. This article investigates two more recent accounts dealing with engaged Buddhism — David Loy’s The Great Awakening and Sallie B. King’s Socially Engaged Buddhism — in order to critique and ultimately to go beyond Yarnall’s categories. It touches on questions concerning the legitimacy and obligations of scholars in defining Buddhism for practitioners and for fellow academics, and makes the case that a significant shift is needed in order to avoid problems of Orientalism at work in some academic accounts of engaged Buddhism.